The Masturbation Erection Index (MEI): validation of a new psychometric tool, derived from the six‐item version of the International Index of Erectile Function (IIEF‐6) and from the Erection Hardness Score (EHS), for measuring erectile function during masturbation. (23rd October 2018) - Limoncin, Erika; Gravina, Giovanni L.; Lotti, Francesco; Maseroli, Elisa; Ciocca, Giacomo; Corona, Giovanni; Maggi, Mario; Reisman, Yacov; Balercia, Giancarlo; Lenzi, Andrea; Jannini, Emmanuele A.
Abstract : Objectives: To validate a psychometric instrument, the Masturbation Erection Index (MEI) able to evaluate erectile function (EF) during masturbation. In fact, although the evaluation of EF during masturbation is pivotal in evaluating erectile dysfunction (ED), to date no specific psychometric tools have been developed to measure it both in the routine clinical practice and in the experimental setting. Patients and Methods: Of 560 men attending our andrological outpatient clinic for the first time, 99 (17.7%) had ED. As a control group, we enrolled 102 sexually healthy men. All the men were requested to complete both the six‐item version of the International Index of Erectile Function (IIEF‐6) and the MEI. The MEI was used together with a standardised tool, the Erection Hardness Score (EHS). The MEI was validated in terms of content validity. Test–retest reliability was assessed using the intraclass correlation coefficient (ICC). Internal consistency was evaluated by Cronbach's α. The comparability between the MEI and IIEF‐6 in measuring EF was tested by Bland–Altman analysis. The concordance correlation coefficient (CCC) between the two questionnaires was also determined. Results: Internal consistency of the MEI was >0.93. Test–retest reliability was 0.982 (95% confidence interval [CI] 0.975–0.987). Bland–Altman analysis showed a good level of agreement between the IIEF‐6 and MEI in the whole ED population, with stronger agreement in the organic‐ED subpopulation. The estimated area under the curve of the MEI was 0.983 ( P < 0.001; 95% CI 0.954–0.996), with a score of ≤27 as the optimal threshold to discriminate between the presence and absence of ED during self‐induced masturbation. The CCC, Pearson ρ and bias correction factor (Cb) were 0.951 (95% CI 0.936–0.962), 0.968, and 0.982, respectively. Conclusion: The MEI showed good internal consistency and a good level of agreement with the IIEF‐6. Hence, the MEI fulfills the major psychometric requirements for measuring EF during masturbation.